![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{2^{10}.9^6}{4^6.3^{11}}=\frac{2^{2.5}.3^{2.6}}{4^6.3^{11}}=\frac{\left(2^2\right)^5.3^{12}}{4^6.3^{11}}=\frac{4^5.3^{12}}{4^6.3^{11}}=\frac{3}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{10+5}{4.5}=\frac{15}{20}=\frac{3}{4}\)
\(\frac{2^2.9}{27.3}=\frac{4.9}{27.3}=\frac{36}{81}=\frac{4}{9}\)
k mk nha!!!
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{-7^5.4^9}{-49.2^8}\)
\(=\frac{-7^5.\left(2^2\right)^9}{-7^2.2^8}\)
\(=\frac{-7^5.2^{18}}{-7^2.2^8}\)
\(=7^3.2^{10}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{3^{10}.\left(-5\right)^{21}}{\left(-5\right)^{21}.3^{12}}\)\(=\)\(\frac{1}{3^2}\)\(=\frac{1}{9}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, ta có \(\frac{2.\left(-13\right).9.10}{\left(-3\right).4.\left(-5\right).26}\)=\(\frac{2.\left(-13\right).\left(-3\right).\left(-3\right).2.\left(-5\right)}{\left(-3\right).2.2.\left(-5\right).\left(-2\right).\left(-13\right)}\)
rút gọn đi còn: \(\frac{-3}{-2}\)=\(\frac{3}{2}\)
a)4/5
b)2/5